PENGARUH INTELLECTUAL CAPITAL DISCLOSURE DAN VALUE ADDED INTELLECTUAL COEFFICIENCY TERHADAP FIRM PERFORMANCE - Brian Edbert Yonathan; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examine the influence of intellectual capital disclosure and value added intellectual coefficiency on firm performance. This study used firm size, sales growth, and firm age as control variables. The sample consisted of 114 manufacture companies listed on Indonesia Stock Exchange during the period of 2010- 2015. The data was collected from annual reports, then analyzed using GRETL software.The result revealed that there was positive influence of intellectual capital disclosure and value added intellectual capital coefficient on firm performance. However this study failed to find the influence of sales growth on firm performance. Moreover, this study also revealed that there was positive inluence of firm size and firm age on firm performance.